Local Exhaust Ventilation and Application: A Review - Hasan, Nor Halim; Said, M. R; Leman, A.M (IJENS, 2012)
The industries that are involved in the production of dangerous chemicals requires Local Exhaust Ventilation (LEV) for separating employees to hazards. LEV purpose is to separate contaminants from the source it generated. The objective of this paper is to look at a number of studies related to the LEV and its applications. The discussions are divided to several parts such as application in construction industries, buildings, manufacturing industries, workshops and paint manufacturers. Ongoing monitoring, maintenance and effective personal protective equipment (PPE) are necessary to ensure the spray booths can be managed properly and avoid employee exposure to contaminants. Ventilation design in buildings, equipment selection and use of Computational Fluid Dynamics (CFD) is highly suggested in that application. There are no exposures to hazardous materials to the building users in the construction of hospitals and others. Use of push-pull ventilation method is an efficient. The future phase of ventilation system in airplanes and hawker centre will be the consumer's attention.